The Institutional Process of Repatriation of Indigenous Heritage: The Case of the Sami Drum Freavnantjahke gievrie - Opitz, Swantje (UiT Norges arktiske universitet, 2023)
This paper addresses the repatriation debate about the South Sami Freavnantjahke gievrie that was taken from its owner, the Sami Bendix Andersen Frennings Fjeld, in 1723 by the missionary Thomas von Westen. After the confiscation, the drum came to the Danish royal family and was gifted in 1757 to the noble family Saxony-Hildburghausen in what is now Thuringia, Germany. Today the gievrie is in possession of the Meininger Museen. In 2017, the drum was exhibited on loan in Trondheim at the exhibition "Hvem eier historien?" [Who owns history?], which was the impetus for the repatriation debate. The South Sami Museum Saemien Sijte requested a meeting with the German museum in 2021 to discuss a repatriation of the drum. This thesis explores the different perspectives of Saemien Sijte and the Meininger Museen on the Freavnantjahke gievrie, its value to their institutions and the affects that its repatriation could have on their respective communities. Through interviews with the museum directors, Dr. Birgitta Fossum and Dr. Philipp Adlung, their positions on repatriation, identity, traditional knowledge, colonization as well as decolonization in relation to museums are presented. The drum’s contemporary value for the South Sami community is examined in context of Sami history, previous repatriation projects of Sami cultural heritage and research by non-Sami scholars. Through the insight into the interest of both institutions in managing and displaying the drum this work seeks to identify the challenges and opportunities that the repatriation of the Freavnantjahke gievrie entails and contribute to the debate.